The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1126/science.aar4851
|View full text |Cite
|
Sign up to set email alerts
|

Giant tunneling magnetoresistance in spin-filter van der Waals heterostructures

Abstract: Magnetic multilayer devices that exploit magnetoresistance are the backbone of magnetic sensing and data storage technologies. Here, we report multiple-spin-filter magnetic tunnel junctions (sf-MTJs) based on van der Waals (vdW) heterostructures in which atomically thin chromium triiodide (CrI) acts as a spin-filter tunnel barrier sandwiched between graphene contacts. We demonstrate tunneling magnetoresistance that is drastically enhanced with increasing CrI layer thickness, reaching a record 19,000% for magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
929
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,019 publications
(1,007 citation statements)
references
References 40 publications
40
929
2
4
Order By: Relevance
“…In fact, “vdW‐MTJs” have been successfully fabricated, an example of which is based on a graphite/CrI 3 /graphite sandwich structure that possesses a large tunneling magnetoresistance . Figure A shows a schematic of such vdW‐MTJ with bilayer CrI 3 functioning as a spin‐filter . The magnetic‐field‐dependent tunneling current at a selected bias voltage and RMCD signal are shown in Figure B, from which a double spin filter effect is evident: in the antiparallel spin states at low field, the current is small because of suppressed spin‐conserving tunneling of an electron through the adjacent layers .…”
Section: Progress On Van Der Waals Magnets and Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, “vdW‐MTJs” have been successfully fabricated, an example of which is based on a graphite/CrI 3 /graphite sandwich structure that possesses a large tunneling magnetoresistance . Figure A shows a schematic of such vdW‐MTJ with bilayer CrI 3 functioning as a spin‐filter . The magnetic‐field‐dependent tunneling current at a selected bias voltage and RMCD signal are shown in Figure B, from which a double spin filter effect is evident: in the antiparallel spin states at low field, the current is small because of suppressed spin‐conserving tunneling of an electron through the adjacent layers .…”
Section: Progress On Van Der Waals Magnets and Heterostructuresmentioning
confidence: 99%
“…Heterostructures and devices based on 2D‐vdW magnets are expected to possess a great variety of properties with strong application potential. Notable examples include the giant magnetoresistance and spin‐filtering phenomena in 2D spin‐valves and tunnel junctions …”
Section: Introductionmentioning
confidence: 99%
“…Pleasantly, spinfilter MTJs (sf-MTJs) based on different layers of CrI 3 with giant TMR were demonstrated by Song et al [81] Thin graphene flakes were placed on the top and bottom of CrI 3 , and the structure contains h-BN flakes to avoid the degradation (Figure 14a). Pleasantly, spinfilter MTJs (sf-MTJs) based on different layers of CrI 3 with giant TMR were demonstrated by Song et al [81] Thin graphene flakes were placed on the top and bottom of CrI 3 , and the structure contains h-BN flakes to avoid the degradation (Figure 14a).…”
Section: Cri 3 -Based Spin-filter Mtj With Giant Tmrmentioning
confidence: 99%
“…They adopted scalable techniques, which did not require the transfer of h-BN flakes. [81] Copyright 2016, AAAS. The CVD-grown h-BN possessed many grain boundaries (GBs) that provided thin defective paths for the formation of filaments and the GBs per cell are controllable by tuning CVD growth parameter.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…According to the Mermin–Wagner theorem,18 2D long‐range FM order cannot exist in an isotropic magnetic system. Recently, people found that 2D layered CrI 3 ,19–27 Cr 2 Ge 2 Te 6 ,28 and CrSiTe 3 29 possesses intrinsic magnetocrystalline anisotropy against thermal fluctuations. However, the Curie temperatures of CrI 3 , Cr 2 Ge 2 Te 6 , and CrSiTe 3 are only dozens of Kelvins.…”
Section: Introductionmentioning
confidence: 99%